Nonmonotonic Change of the Arctic Ocean Freshwater Storage Capability in a Warming Climate. Issue 10 (25th May 2021) - Wang, Shizhu; Wang, Qiang; Shu, Qi; Song, Zhenya; Lohmann, Gerrit; Danilov, Sergey; Qiao, Fangli
Abstract: Freshwater in the Arctic Ocean is one of the key climate components. It is not well understood how the capability of the Arctic Ocean to store freshwater will develop when freshwater supplies increase in a warming climate. By using numerical experiments, we find that this capability varies with the Arctic sea ice decline nonmonotonically, with the largest capability at intermediate strength of sea ice decline. Through enhancing the ocean surface stress, sea ice decline not only accumulates freshwater toward the Amerasian Basin but also tends to reduce the amount of freshwater in both the Eurasian and Amerasian basins by increasing the occupation of Atlantic‐origin water in the upper ocean. An increase in river runoff modulates the counterbalance of the two competing effects, leading to the nonmonotonic changes of the Arctic freshwater storage capability in a warming climate. Plain Language Summary: The Arctic Ocean is a giant freshwater pool of the Earth System. In a warming climate, the Arctic liquid freshwater content is expected to increase because more freshwater tends to be hosed into the Arctic Ocean. Will the Arctic freshwater storage capability change? In this work, we conducted numerical experiments to show that sea ice is a key controller of the Arctic freshwater storage capability. With the shrinking sea ice, more freshwater is transported from the Eurasian Basin to the Amerasian Basin. In the meanwhile, more saline water fills up the Eurasian Basin and further propagates to the Amerasian Basin too. The opposite effects of these two processes cause a first increasing and then decreasing change in the Arctic freshwater content following the strengthening of the sea ice decline. However, the increase of river runoff can delay the transition between the two phases, leading to a bell‐shaped Arctic freshwater storage capability: the maximum capability occurs at moderate strength of sea ice loss. Our study suggests that the impact of sea ice decline should be adequately considered when predicting changes in Arctic Ocean environment and its changing role in the climate. Key Points: Sea ice decline leads to both enhanced freshwater Ekman transport and increased occupation of Atlantic‐origin water in the Arctic Ocean Counterbalance between the two processes renders a first increasing and then decreasing liquid freshwater content while sea ice declines Stronger river runoff modulates the counterbalance and causes nonmonotonic changes of freshwater storage capability in a warming world